Standardization of early drain removal following pancreatic resection: proposal of the “Ottawa pancreatic drain algorithm” - Smith, Heather; Balaa, Fady K; Martel, Guillaume; Abou Khalil, Jad; Bertens, Kimberly A (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Early drain removal after pancreatic resection is encouraged for individuals with low postoperative day 1 drain amylase levels (POD1 DA) to mitigate associated morbidity. Although various protocols for drain management have been published, there is a need to assess the implementation of a standardized protocol. Methods The Ottawa pancreatic drain algorithm (OPDA), based on POD1 DA and effluent volume, was developed and implemented at our institution. A retrospective cohort analysis was conducted of all patients undergoing pancreatic resection January 1, 2016-October 30, 2017, excluding November and December 2016 (one month before and after OPDA implementation). Results 42 patients pre-implementation and 53 patients post-implementation were included in the analysis. The median day of drain removal was significantly reduced after implementation of the OPDA (8 vs. 5 days; p = 0.01). Early drain removal appeared safe with no difference in reoperation or readmission rate after protocol implementation (p = 0.39; p = 0.76). On subgroup analysis, median length of stay was significantly shorter following OPDA implementation for patients who underwent DP and did not develop a postoperative pancreatic fistula (POPF) (6 vs 10 days, p = 0.03). Although the incidence of both surgical site infection and POPF were reduced following the intervention, neither reached statistical significance (38.1 to 28.3%, p = 0.31; and 38.1 to 28.3%, p = 0.31 respectively). Conclusions Implementing the OPDA was associated with earlier drain removal and decreased length of stay in patients undergoing distal pancreatectomy who did not develop POPF, without increased morbidity. Standardizing drain removal may help facilitate early drain removal after pancreatic resection at other institutions.